2007
DOI: 10.1002/mnfr.200700210
|View full text |Cite
|
Sign up to set email alerts
|

A novel method to measure both the reductive and the radical scavenging activity in a linoleic acid model system

Abstract: The aim of this study was to develop a combined method for measuring the total antioxidant activity, the reductive and the radical scavenging activity. Linoleic acid was used as the substrate for an iron-initiated lipid peroxidation to measure the total antioxidant activity. In addition, methyl esters of linoleic acid hydroperoxides were used as substrates to measure the reductive antioxidant activity. The radical scavenging antioxidant activity was calculated by subtracting the reductive antioxidative activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 16 publications
0
16
0
Order By: Relevance
“…The AOX of plasma samples was determined in vitro by measuring their inhibitory effect on linoleic peroxidation closely following the procedure of Bright et al (29), with some modifications as previously reported (30). The results were related to the absorption of a Trolox standard solution in water ethanol and are given as Trolox equivalents.…”
Section: Blood Sampling and Laboratory Measurementsmentioning
confidence: 99%
“…The AOX of plasma samples was determined in vitro by measuring their inhibitory effect on linoleic peroxidation closely following the procedure of Bright et al (29), with some modifications as previously reported (30). The results were related to the absorption of a Trolox standard solution in water ethanol and are given as Trolox equivalents.…”
Section: Blood Sampling and Laboratory Measurementsmentioning
confidence: 99%
“…Most comparisons of the antioxidant activity of fat soluble compounds, e.g. natural ones like carotenoids, lipoic acid or ubiquinones and synthetic antioxidants like 2,6-di-tertbutyl hydroxytoluene (BHT), 2-tert-butyl-hydroxy-anisol (BHA) and hydroxyltyrosol derivatives, were done only with tocopherols or exclusively with a-T [25,[27][28][29][30][31][32][33]. The aim of this study was to compare the different forms of vitamin E concerning their antioxidant activity.…”
Section: Introductionmentioning
confidence: 99%
“…Many research models have been established in chemical and/or biological systems for the studies of mechanisms of action of antioxidants as well as identification of new antioxidants especially from natural substances. Generally, the antioxidant ability was measured and presented as total antioxidant activity [17,18], total antioxidant capacity [19,20], total antioxidant potentials [21], Trolox equivalent antioxidant capacity [22], total radical absorption potentials [23], ferric reducing/antioxidant power [24], and oxygen radical absorption capacity [25]. Mechanistically, these methods are based on either a single-electron transfer reaction or a hydrogen atom transfer reaction from an antioxidant or oxidant to a free radical.…”
Section: Introductionmentioning
confidence: 99%
“…The change of optical absorbance of either antioxidant or oxidant is measured for the quantitation for antioxidant capability. The chemical approaches are simple and easy to study the total antioxidant activity, which includes the radical scavenging ability and reductive activity [18]. Radicals are commonly used to measure the radical scavenging ability of antioxidant.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation